Linkage between mindfulness and the ability to detect weak signals - Nguyen, Hoa (My University, 2020)
Context: The background of this research was the interest in the relationship between deep self-reflection with the ability to spot early signs of change. Mindfulness is considered as a useful practice for self-reflection from contemplating the body, feelings and emotions, thoughts, behaviors, and the object of the mind. Mindfulness characteristics were assumed to link with the ability to detect weak signals. Objective: The main purpose of the thesis was to explore the linkages between mindfulness practice and abilities to detect weak signals. Two questions guided the experiment: (1) What are factors that can elevate abilities to detect weak signals? and (2) How does mindfulness practice link with these abilities? Design: An online questionnaire included three parts. The first part was the 28-item instrument measuring five mindfulness characteristics. The second part included 28 items assessing sensitivity, creativity, and courage with respect to weak signal detection. The third part included demographic questions. Participants: 116 mindfulness practitioners from Palouse Mindfulness Student Community, Mindfulness Community in Finland (Mindfulness Suomi) and Plum Village communities. Method: Quantitative analysis was conducted to explore factors and their linkage with mindfulness. Specific techniques used in the analysis included factor analysis, cor-relation, subsets regression, Kruskal-Wallis test and Mann-Whitney test with Bonferroni correction. Results: The findings showed the linkage between mindfulness characteristics and sensitivity, creativity, and courage – the three abilities to detect weak signals. Factors that possibly elevated abilities to detect weak signals included interpersonal awareness, self-awareness, intrinsic playfulness, connecting phenomena, inner security, observing inner experience, describing, attention and concentration, non-judgment, and non-reactivity. Interpersonal awareness and self-awareness were the factors of sensitivity. Intrinsic playfulness and connecting phenomena were the factors of creativity and inner security was the factor of courage. Results found that five mindfulness characteristics tended to correlate with the five factors of three abilities to detect weak signals. Of the five mindfulness characteristics, observing current experience and non-reactivity had the dominant effects on the three abilities whereas non-judgment, attention and concentration and describing showed a weak tendency.
Keywords: Mindfulness, Weak signals, Sensitivity, Creativity, Courage, Awareness, Non-reactivity, Non-judgment, Attention and concentration, Describing